Implementation Of Pancasila Ideology Development And Pancasila Ideology Development Policy Regulation And Training Policies - Dina Widya Astuti; Nurliah Nurdin; Eko Budi Santoso (Sean Institute, 2024)
The true essence of Pancasila is not only knowing and memorizing the precepts in Pancasila, but Pancasila needs to be actualized in the moral attitudes and behavior of all Indonesian citizens. Every citizen needs to realize that in society, nation and state, every citizen has human nature, that every human being is both an individual creature and a social creature. This research uses a descriptive qualitative approach. The data used in this research is divided into two types, namely primary data and secondary data. The informants in this study were 11 people. Data analysis that has been developed by Miles and Huberman uses an interactive model with three procedures, namely: Data Reduction, Data Presentation and Conclusion Drawing. research results and discussion: The implementation of educational regulations and training for Pancasila ideology development seen from the productivity dimension is currently not optimal because the Pancasila Ideology Development Agency (BPIP) does not have office representatives in the regions and seems to work alone and is unable to reach the needs of the target group. Meanwhile, within the internal scope, BPIP has not yet fully realized the mandate of Presidential Regulation Number 7 of 2018